(untitled) (International Journal of Environmental Sciences, 2025)
Five types of polymers containing thiadiazol moiety within their backbone were prepared. Azomethine and azo groups are inserted in the backbone of the polymers. The chemical structures of polymers were studied by using FTIR, also the thermal analysis are measured by TGA method. The electrical conductivity of the prepared polymers were studied. It was shown that the chemical structure of the polymers play the major role affected on the electrical conductivity. The results showed that azomethine and azo groups enhanced the electrical conductivity many times. On the other hand the azomethine moiety increase the electrical conductivity more than that of azo. The results reveals that the amide linking group can enhanced the electrical conductivity more than the ester linking group. Doping the synthesized polymers with two type of dopant (NaI and I2) was accomplished with different ratios. The electrical conductivity of the doped polymers were increased significantly.